Psychological distress and psychiatric disorder after natural disasters: systematic review and meta-analysis - Beaglehole, Ben; Mulder, Roger T.; Frampton, Chris M.; Boden, Joseph M.; Newton-Howes, Giles; Bell, Caroline J. (British journal of psychiatry, 2018)
Natural disasters are increasing in frequency and severity. They cause widespread hardship and are associated with detrimental effects on mental health.AimsOur aim is to provide the best estimate of the effects of natural disasters on mental health through a systematic review and meta-analysis of the rates of psychological distress and psychiatric disorder after natural disasters. This systematic review and meta-analysis is limited to studies that met predetermined quality criteria. We required included studies to make comparisons with pre-disaster or non-disaster exposed controls, and sample representative populations. Key studies were identified through a comprehensive search of PubMed, EMBASE and PsycINFO from 1980 to 3 March 2017. Random effects meta-analyses were performed for studies that reported key outcomes with appropriate statistics. Forty-one studies were identified by the literature search, of which 27 contributed to the meta-analyses. Continuous measures of psychological distress were increased after natural disasters (combined standardised mean difference 0.63, 95% CI 0.27-0.98, P = 0.005). Psychiatric disorders were also increased (combined odds ratio 1.84, 95% CI 1.43-2.38, P < 0.001). Rates of post-traumatic stress disorder and depression were significantly increased after disasters. Findings for anxiety and alcohol misuse/dependence were not significant. High rates of heterogeneity suggest that disaster-specific factors and, to a lesser degree, methodological factors contribute to the variance between studies. Increased rates of psychological distress and psychiatric disorders follow natural disasters. High levels of heterogeneity between studies suggest that disaster variables and post-disaster response have the potential to mitigate adverse effects.Declaration of interestNone.